Language Loss and Refugee Identity: A Pedagogical Reading of Jan Dost’s A Handful of Dirt - Abdus Salam; Mahfuza Rahat Oishy (Mauve Journal De Leardu, 2024)
The short story A Handful of Dirt by Jan Dost vividly portrays the refugee experience, focusing on alienation, language loss, and the psychological burden of displacement. Refugees often struggle to adapt to new environments, and communication barriers intensify their sense of isolation. This study seeks to analyze how Dost’s narrative reflects these linguistic and emotional challenges while drawing educational implications for language teaching. Employing a qualitative text-based method, the analysis explores the protagonist’s inability to master the host country’s language, his attempts to preserve his mother tongue, and his anthropomorphic conversations with inanimate objects as a coping strategy. These narrative elements reveal how language is inseparable from identity and belonging. The findings highlight the pedagogical value of refugee literature in language education. Dost’s story underscores the need for culturally responsive teaching, mother-tongue maintenance, and empathy-driven curricula for refugee learners. By incorporating such narratives, educators can foster awareness, inclusivity, and emotional engagement in classrooms. In conclusion, A Handful of Dirt serves not only as a literary depiction of exile but also as a resource for understanding and improving language education practices in multicultural contexts.